O ensino do sistema respiratório através da contextualização e de atividades práticas - Ruppenthal, Raquel (2013)
This study was conducted in a city whose main economic activity is tobacco farming, which contributes to much of the population is exposed to smoke and pesticides that end up being inhaled during breathing. In this context, the study of the respiratory system should help that individuals may have attitudes that ensure the health. Thus, this study investigated whether the use of contextualized situations and practical activities during the study of the respiratory system contribute to explaining modify profiles of students in relation to the respiratory system. Data collection was conducted through analysis of science textbooks of the early years to build a profile explaining that students of 8 th year could have on the respiratory system and questionnaires before the study of the respiratory system, after a theoretical study with contextualized situations, after practical activities and after six months. It was found that textbooks are improving, but they still have some misconceptions, and others treat the study of the respiratory system superficially. Furthermore, not all goals have proposed teaching strategies for their achievement. Moreover, to reach the 8th year, the explanations of the students are strongly vitalistic and have few details in their explanations. After conducting classes using contextualized situations and practical activities, explanations reached higher levels, with stamp and some mechanistic explanations reach the ultrastructural level. After six months, it was found that although most of the responses have come back to the vitalistic and mechanistic level, continue using concepts of the respiratory movements, composition of air, gas exchange and energy production in their explanations. Thus, it can be stated that the use of contextualized situations and practical activities, and motivate students also contribute to modify the explanatory levels of students in relation to the respiratory system.